Effects of the adhesive layer on the multi-hit ballistic performance of ceramic/metal composite armors - Yonghua Shen; Yangwei Wang; Shaofeng Du; Zhikun Yang; Huanwu Cheng; Fuchi Wang (Journal of Materials Research and Technology, 2021)
The effects of adhesive layer on the multi-hit ballistic performance of ceramic/metal composite armors are studied by the experimental and numerical methods. The types (epoxy and polyurethane), bonding performance (bonding strength and failure displacement) and thickness, ranging from 0.2 to 3.0 mm, of adhesive layer are systematically investigated for exploring the responses on the projectile, the ceramic and the backing plate. The results show that the epoxy targets exhibit slightly better single-hit ballistic performance than the polyurethane targets. The polyurethane targets display superior multi-hit ballistic performance. However, the residual penetration depth of the backing plate in the second penetration becomes larger owing the extensive damage in the surrounding ceramic tiles. The detached ceramic area decreases sharply with the increase of bonding strength and failure displacement. In addition, compared with the bonding strength, the failure displacement is more sensitive to the detachment of ceramic. The results show that with the increase of adhesive layer thickness, the time of ceramic unsupported by the backing plate becomes longer, making the ballistic performance of the ceramic poor. The adhesive layer thickness has contrary effects on the ballistic resistance and the damage area of ceramic. The optimal adhesive layer thickness with the better multi-hit ballistic performance is 2.0 mm.